2022
DOI: 10.48550/arxiv.2203.14465
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STaR: Bootstrapping Reasoning With Reasoning

Abstract: Generating step-by-step "chain-of-thought" rationales improves language model performance on complex reasoning tasks like mathematics or commonsense question-answering. However, inducing language model rationale generation currently requires either constructing massive rationale datasets or sacrificing accuracy by using only few-shot inference. We propose a technique to iteratively leverage a small number of rationale examples and a large dataset without rationales, to bootstrap the ability to perform successi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Language models (LMs) have demonstrated impressive few-shot learning abilities (Brown et al, 2020;Chowdhery et al, 2022). This has led to a number of proposals to use LMs as the basis of informal reasoning, including scratchpads (Nye et al, 2021), chain of thought prompting (Wei et al, 2022;Wang et al, 2022), learned verifiers (Cobbe et al, 2021), selection-inference (Creswell et al, 2022), and bootstrapping (Zelikman et al, 2022). They have also been applied in formal mathematics settings to guide theorem provers (Polu & Sutskever, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Language models (LMs) have demonstrated impressive few-shot learning abilities (Brown et al, 2020;Chowdhery et al, 2022). This has led to a number of proposals to use LMs as the basis of informal reasoning, including scratchpads (Nye et al, 2021), chain of thought prompting (Wei et al, 2022;Wang et al, 2022), learned verifiers (Cobbe et al, 2021), selection-inference (Creswell et al, 2022), and bootstrapping (Zelikman et al, 2022). They have also been applied in formal mathematics settings to guide theorem provers (Polu & Sutskever, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1a); 2) approaches that encourage LLMs to produce reasoning explicitly, but all reasoning steps are produced in one generative step (Cobbe et al, 2021;Dalvi et al, 2021;Jhamtani and Clark, 2020;Nye et al, 2021a;Wei et al, 2022;Zelikman et al, 2022) (e.g. Fig.…”
Section: Related Workmentioning
confidence: 99%
“…However, although explicit reasoning helps improve the accuracy of the models, encouraging the models to produce multiple steps of reasoning in a single generative pass is not enough to make the models use reasoning in a causal manner. The authors found that the generated reasoning traces often contain unrelated or incorrect steps while still resulting in the correct answer (see examples in the appendices of (Wei et al, 2022;Zelikman et al, 2022)). Encouraging LLMs to generate each reasoning step one at a time is currently the most promising direction for achieving causal reasoning, and it is the approach we take in our paper.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work utilized the ability of large LMs to generate intermediate reasoning steps for improving performance on QA tasks Zelikman et al, 2022;Nye et al, 2022). Specifically, introduced a 'chain-of-thought' prompting, to elicit intermediate reasoning steps along with answers from LMs, which improved performance on several reasoning tasks.…”
Section: Related Workmentioning
confidence: 99%